2015
DOI: 10.1016/j.marenvres.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Sessile and mobile components of a benthic ecosystem display mixed trends within a temperate marine reserve

Abstract: Despite recent efforts to increase the global coverage of marine protected areas (MPAs), studies investigating the effectiveness of marine protected areas within temperate waters remain scarce. Furthermore, out of the few studies published on MPAs in temperate waters, the majority focus on specific ecological or fishery components rather than investigating the ecosystem as a whole. This study therefore investigated the dynamics of both benthic communities and fish populations within a recently established, ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…Therefore, as we could not employ a before-after BACI approach (Hilborn et al, 2004;Sale et al, 2005), we monitored crustacean populations within the reserve and in several control areas over a period of four years. This was done on the assumption that a divergence in population characteristics over time would be indicative of an effect (see Howarth et al, 2015aHowarth et al, , 2015b.…”
Section: Sampling Designmentioning
confidence: 99%
“…Therefore, as we could not employ a before-after BACI approach (Hilborn et al, 2004;Sale et al, 2005), we monitored crustacean populations within the reserve and in several control areas over a period of four years. This was done on the assumption that a divergence in population characteristics over time would be indicative of an effect (see Howarth et al, 2015aHowarth et al, , 2015b.…”
Section: Sampling Designmentioning
confidence: 99%
“…Given the uniqueness of the Lamlash Bay NTZ as the only highly protected marine reserve in Scotland, and the availability of scientifically documented evidence of ecological recovery within the NTZ boundaries (Figures 4, 5, Howarth et al, 2011Howarth et al, , 2015aHowarth et al, ,b, 2016, the NTZ played a key role in making the case for designating the South Arran MPA and other MPAs throughout Scotland (COAST, 2012). More significantly, COAST's campaigns and collaborations with scientists have been vital for ensuring the new MPAs receive adequate protection, ensuring a lasting and far-reaching legacy.…”
Section: -Presentmentioning
confidence: 99%
“…Annual photo-quadrat surveys between 2011 and 2013 revealed a variety of seabed habitats, such as sponges and macroalgae, had become more abundant within Lamlash Bay NTZ than adjacent areas (Howarth et al, 2015a). Diver transects found that the recovery of these habitats had increased the abundance of juvenile scallops by two to five times compared to neighboring fishing grounds (Howarth et al, 2015b).…”
Section: Monitoring Of Lamlash Bay Ntz: 2010-presentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that sediment and biota samples collected in the Bay demonstrated that EUNIS classification is useful at some levels for specific habitats; however, the biotic composition of other areas were found to be sufficiently different from those described in EUNIS that a total of 13 potentially new classes were identified by the authors. Benthic habitats and biotopes off the coast of Norway were modeled using video transectHowarth et al 2015a). While data collected from diver surveys, video surveys, and photographic analysisindicated that several epifaunal assemblages were significantly more abundant within the reserve, no statistical difference in fish abundance was detected within the reserve compared to outside of the reserve.…”
mentioning
confidence: 99%